Affections of Hurricane OTIS and Its Impact on Human Rights - García Sánchez, Dr. María del Rocío; López , Dr Noemi Ascencio; Añorve, Dr Joaquín Reyes; Godínez Alarcón., Mtra Guadalupe (International Journal of Scientific Research and Management (IJSRM), 2024)
The fury of Hurricane OTIS on October 24, 2023 exposed pre-existing social inequalities and inequities in Acapulco, Guerrero, Mexico. OTIS also evidenced the omissions before the hurricane, the abandonment during the hurricane and the inabilities after the hurricane of the authorities in charge of protecting society. The actions of the three levels of government were reprehensible before and after the impact of the hurricane. First, because there was no timely warning plan, the places of refuge were not made known, much less the level of destruction that the hurricane would cause. And after the hurricane, there was no response plan or protocols to respond to the most basic needs and protect citizens. This work was carried out under an inductive-deductive method in which a documentary review of national and international legislation was carried out, as well as literature related to the topic of research on natural disasters and human rights after Hurricane OTIS in Acapulco, Guerrero. , Mexico. The problems that subsequently prevailed and that affected the human rights of citizens were primarily the lack of prevention, safety and security, health, work, housing, public services, pollution and unequal access in the provision of aid. Definitely, aid in an emergency situation due to a natural disaster must be based on the perspective of human rights in order to provide relevant and effective assistance that fully meets all the basic needs of the victims for their prompt recovery and reconstruction.